Agomelatine Augmentation of Escitalopram Therapy in Treatment-Resistant Obsessive-Compulsive Disorder: A Case Report - De Berardis, Domenico; Serroni, Nicola; Marini, Stefano; Martinotti, Giovanni; Ferri, Francesca; Callista, Gaetano; La Rovere, Raffaella; Moschetta, Francesco Saverio; Di Giannantonio, Massimo (Case Reports in Psychiatry, 2012)
Obsessive-compulsive disorder (OCD) is a chronic condition characterized by obsessions or compulsions that cause distress or interfere with functioning. Selective serotonin reuptake inhibitors are the first-line strategy in the treatment of OCD, but approximately 40% to 60% of patients with OCD fail to respond to them. Several augmentation strategies have been proposed, including the use of atypical antipsychotics and antidepressant combinations. In the present paper we describe the case of a young female patient suffering from severe treatment-resistant OCD who remitted as a result of agomelatine augmentation of escitalopram therapy.